Aortic regurgitation and sinus of Valsalva-right atrial fistula after blunt thoracic trauma. Issue 4 (October 1982) - Rehr, R B; Mack, M; Firth, B G
Abstract : Non-penetrating chest trauma commonly causes a wide variety of cardiac injuries. Disruption of the aortic valve with resultant aortic regurgitation is not uncommon; conversely, a sinus of Valsalva-right atrial fistula, in the absence of a congenital sinus of Valsalva aneurysm, has been reported only once previously. This report describes the detection by preoperative cardiac catheterisation of both aortic regurgitation, and a sinus of Valsalva-right atrial fistula after blunt chest trauma, and its surgical management. The need for preoperative cardiac catheterisation in patients suffering from non-penetrating cardiac trauma is emphasised, even when the diagnosis appears cleas, because of the diverse nature and possible multiplicity of cardiac lesions.